2019
DOI: 10.1186/s12934-019-1208-8
|View full text |Cite
|
Sign up to set email alerts
|

A systematic approach to study the pH-dependent release, productivity and product specificity of dextransucrases

Abstract: Background Dextransucrases are extracellular enzymes, which catalyze the formation of α-1→6-linked glucose polymers from sucrose. These enzymes are exclusively expressed by lactic acid bacteria, which commonly acidify the extracellular environment due to their physiology. Dextransucrases are thus confronted with steadily changing reaction conditions in regards to the environmental pH, which can further affect the amount of released dextransucrases. In this work, we studied the effect of the env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

5
3

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 41 publications
4
23
0
Order By: Relevance
“…The yield, size and functional properties of levan from G. albidus TMW 2.1191 can be influenced by modulation of the environmental pH, as demonstrated in the present study and a previous study [20]. Similar findings were obtained for the dextran produced by Lactobacillus hordei TMW 1.1822 [33]. The environmental pH is, therefore, decisive to trigger the properties of uncharged, water-soluble high-molecular-weight exopolysaccharides produced by glucansucrases or fructansucrases [34].…”
Section: Discussionsupporting
confidence: 88%
“…The yield, size and functional properties of levan from G. albidus TMW 2.1191 can be influenced by modulation of the environmental pH, as demonstrated in the present study and a previous study [20]. Similar findings were obtained for the dextran produced by Lactobacillus hordei TMW 1.1822 [33]. The environmental pH is, therefore, decisive to trigger the properties of uncharged, water-soluble high-molecular-weight exopolysaccharides produced by glucansucrases or fructansucrases [34].…”
Section: Discussionsupporting
confidence: 88%
“…The yield, size and functional properties of levan from G. albidus TMW 2.1191 can be influenced by modulation of the environmental pH as demonstrated in a previous study [19]. Similar findings were obtained for the dextran produced by Lactobacillus hordei TMW 1.1822 [30]. The environmental pH is hence decisive to trigger the properties of uncharged, water-soluble high-molecular weight exopolysaccharides produced by glucan-or fructansucrases [31].…”
Section: Discussionsupporting
confidence: 77%
“…However, little is known about the influencing factors of levansucrase release as well as of levansucrase activity, both of which are crucial for the efficiency of the complex production process of polydisperse levan taking place under continuously changing conditions. By application of the developed buffer system it was confirmed that the levansucrase is constitutively expressed by G. albidus TMW 2.1191 (without induction by its substrate sucrose) as reported for some dextransucrases secreted by water kefir LAB Schmid et al 2019). Higher volumetric levansucrase activities were detected in buffer supernatants at higher release pH (Fig.…”
Section: Discussionsupporting
confidence: 73%
“…A growth phase-dependent expression of levansucrases was also reported for the enteric bacterium Rahnella aquatilis (Seo et al 2002), at which it has to be considered that expression and secretion/release of sucrases are in fact independent processes. For instance, the water kefir isolate Lactobacillus hordei TMW 1.1822 releases its sucroseconverting dextransucrases in similar amounts into the environment in dependence of sucrose, but independently of the applied environmental release pH while accumulating the dextransucrases within the cell independent of sucrose Schmid et al 2019). In case of Lactobacillus hordei TMW 1.1822 it was further observed that the release pH affects the mean activity/productivity of the dextransucrase at different pH.…”
Section: Discussionmentioning
confidence: 99%